Supervivencia de Rhizobium trifolii en tres portadores - Munévar Martínez, Fernando; Graham, Peter H. (1977)
The survival of Rhizobium trifolii (strain CIAT 61) in three carriers was studied. The rhizobial cells did not survive in "cachaza" (a froth obtained when sugar cane juice is boiled in refineries). The survival in peat and coal was good, at least until 120 days after the inoculation. Coal seems to be slightly better as inoculum carrier than peat. The differences in cell numbers in the three carriers were statistically significant. The low survival in "cachaza" may be due to its high acidity. Studying the survival of other species of Rhizobium in coal is suggested to confirm the suitability of this material as legume inoculum carrier